Conocimiento y grado de ansiedad del familiar del paciente crítico hospitalizado Hospital III EsSALUD Chimbote - Reyes Arteaga, Mirtha Evelin (2023)
The present descriptive correlational research was carried out in order to determine the relationship between the level of knowledge and the degree of anxiety of the family member of the critical patient hospitalized between August and September 2019 in the Intensive Care Unit of Hospital III EsSalud Chimbote with a sample population of 60 relatives who met the inclusion criteria, to whom two instruments were applied, one referring to the level of knowledge of the family member and the second an anxiety scale, both applied to the family member of the hospitalized patient to measure the In relation to this, the test was used, Kendall's Tau b reaching the following conclusions: 47.5% of the family members report a poor and regular level of knowledge about their situation of their hospitalized patient in a critical situation and only 5% manifest good knowledge. 62.5% of the family members have a moderate degree of anxiety, 37.5% severe, they do not present a mild degree of anxiety. Applying the statistical test of Kendall's Tau b = 0.212 p = 0.158, it is not significant, there is no relationship between variables